Advances in Neonatal Intensive Care Technologies for Extremely Premature Infant Survival Improvement - P, Dr. Jayakumar; Kumar K, Dr. Senthil; Dhanraj, Fabiola M; S, Joshua (Adolescência e Saúde, 2026)
Background: Extremely premature infants (<28 weeks gestation) are at high risk of mortality and long-term morbidity due to respiratory insufficiency, infections, neurological complications and immature organ systems. Improvements in neonatal intensive care technologies have altered the survival outcomes and quality of care for this vulnerable population. Objective: To assess the influence of modern neonatal intensive care technologies on survival improvement and clinical outcomes of the extremely premature infants. Methodology: A narrative review was conducted, utilizing published literature from major medical databases. The key technological interventions explored include advanced respiratory support systems, non-invasive ventilation, high frequency oscillatory ventilation, neonatal monitoring devices, AI assisted clinical decision systems, infection-control technologies and developmental care innovations. Findings: Review of recent studies showed significant improvements in neonatal survival and morbidity reduction. The adoption of advanced respiratory technologies was associated with a 25-35% reduction in severe bronchopulmonary complications. Continuous monitoring systems improved early detection of critical events by ~30%. AI-assisted clinical decision tools increased diagnostic accuracy by 20-28 per cent. The survival of extremely premature infants in tertiary neonatal intensive care units increased from about 72% to 88% with integrated technological approaches. Also, consistent reports of reductions in hospital-acquired infections and improved neurodevelopmental outcomes were noted. Conclusion: Technological advances in neonatal intensive care have greatly improved survival and health outcomes for extremely premature infants. We expect that the further integration of precision monitoring, artificial intelligence and advanced respiratory support systems will further enhance the quality of neonatal care and long-term developmental outcomes.